2020
DOI: 10.21873/anticanres.14199
|View full text |Cite
|
Sign up to set email alerts
|

Association of Triiodothyronine Levels With Prostate Cancer Histopathological Differentiation and Tumor Stage

Abstract: Background/Aim: The aim of this study was to determine the association between total triiodothyronine (T3), free fraction of thyroxin (FT4), and thyrotropin (TSH) levels with prostate cancer histopathological features. Patients and Methods: Blood samples from 140 patients with prostate cancer were analyzed preoperatively and stratified according to postoperative histopathological differentiation. The first group (N=62) included patients with prostate cancer Grade Groups (GG) 1-2, while the second group (N=63) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Recent prospective research also suggests that T3 positively correlates with less differentiated prostate cancer, i.e., higher levels were detected in patients with prostate cancer Grade Groups 3-5 compared with patients with prostate cancer Grade Groups 1-2. Also, higher T3 levels positively correlated with a higher pathologic T stage of the disease, and with a higher tumor percentage involvement [28].…”
Section: Clinical Studies and Resultsmentioning
confidence: 85%
“…Recent prospective research also suggests that T3 positively correlates with less differentiated prostate cancer, i.e., higher levels were detected in patients with prostate cancer Grade Groups 3-5 compared with patients with prostate cancer Grade Groups 1-2. Also, higher T3 levels positively correlated with a higher pathologic T stage of the disease, and with a higher tumor percentage involvement [28].…”
Section: Clinical Studies and Resultsmentioning
confidence: 85%
“…Mondul et al ( 54 ) did not find an association between overall hyperthyroidism and prostate cancer risk (20 cases/75), while several other studies have shown that hyperthyroid subjects ( 53 ) and subjects with low levels of TSH <0.50 mU/L (10 cases/160) ( 50 ) or high physiological levels of free T4 (126 cases/1623) have an increased risk of developing prostate cancer ( 55 ). Moreover, a positive association between T3 levels and prostate cancer aggressiveness, based on the Gleason score, tumor grade, and/or tumor percentage involvement, was reported in euthyroid patients ( 56 , 57 ). Overall, these data suggest that physiological increments of free T4 or subclinical (decrease in TSH levels) and frank hyperthyroidism (decrease in TSH and increase in THs) increase the risk of developing prostate cancer, whereas incremented levels of T3 seem to be associated with more aggressive tumors.…”
Section: Biological Effects Of Thyroid Hormonesmentioning
confidence: 95%
“…In an older study by Lehrer et al, T3 levels and disease recurrence in men treated for localized PCa were assessed, reporting a correlating increasingly higher T3 levels for higher-risk groups (45). THs were also involved in prostate cancer aggressiveness; higher T3 levels were associated with higher prostate cancer grade groups and with higher tumor percentage involvement as well as pT stage on definitive pathology (86). Despite all the reported evidence, the role of THs in prostate function and carcinogenesis has to be still evaluated.…”
Section: The Clinical Point Of Viewmentioning
confidence: 99%